Transporte urbano y emisiones de gases de efecto invernadero en América Latina. Una modelización de las emisiones de la movilidad urbana aplicada a Bogotá y Lima - Thomas, Hugo (2024)
In Latin America, urban transport is a major greenhouse gas emitter, responsible for climate change. Public policies are trying to take into account climate change mitigation within urban planning by means of action plans. However, they lack the tools to calculate the emissions and estimate the effect of the measures they set up. Urban mobility surveys are a relevant source of data to know people’s travel patterns. This article develops an emission modelling methodology based on mobility surveys and characteristics of fuels and vehicles, in order to, but not restricted to, produce data to support public policies. In addition, we use the spatial analysis tools to create maps and cartograms that depict the ecological inequalities in an original way.